1990
DOI: 10.1038/348651a0
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the tRNALeu(UUR) gene associated with the MELAS subgroup of mitochondrial encephalomyopathies

Abstract: Mitochondrial encephalomyopathies are usually divided into three distinct clinical subgroups: (1) mitochondrial myopathy, encephalopathy, lactic acidosis and stroke-like episodes (MELAS); (2) myoclonus epilepsy associated with ragged-red fibres (MERRF); and (3) chronic progressive external ophthalmoplegia (CPEO) including Kearns-Sayre syndrome. Large deletions of human mitochondrial DNA and a transition mutation at the mitochondrial transfer RNALys gene give rise to CPEO including Kearns-Sayre syndrome and MER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
919
2
17

Year Published

1992
1992
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,858 publications
(946 citation statements)
references
References 24 publications
8
919
2
17
Order By: Relevance
“…[9][10][11][12] In contrast, the m.3243A4G mutation causes several major clinical phenotypes of mitochondrial disease such as myopathy, encephalopathy, lactic acidosis, stroke-like episodes, maternally inherited diabetes and deafness, chronic progressive external ophthalmoplegia and mitochondrial diabetes. [31][32][33] However, epidemiological evidence of the prevalence of the patients with the m.3243A4G mutation in the population still has limitations. The patients with m.3243A4G including asymptomatic cases in the general population are thought to be as common as 6.57-16.3 per 100 000.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] In contrast, the m.3243A4G mutation causes several major clinical phenotypes of mitochondrial disease such as myopathy, encephalopathy, lactic acidosis, stroke-like episodes, maternally inherited diabetes and deafness, chronic progressive external ophthalmoplegia and mitochondrial diabetes. [31][32][33] However, epidemiological evidence of the prevalence of the patients with the m.3243A4G mutation in the population still has limitations. The patients with m.3243A4G including asymptomatic cases in the general population are thought to be as common as 6.57-16.3 per 100 000.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that small deletions and/or mutations undetectable on Southern blots may be present and accumulate in mtDNA of Parkinson patients, as is the case in other neurological diseases (mitochondrial encephalomyopathies [21,22] and Lebers hereditary optic neuropathy [23]). Sequence analysis of mtDNA should confirm or exclude the involvement of mitochondrial …”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] The clinical hallmark of MELAS is stroke-like episodes that cause the abrupt onset of focal neurological deficits at a young age. Neuroimaging studies and measurement of blood lactate are useful screening tests for the diagnosis of MELAS, though the definite diagnosis of MELAS relies on the ragged red fibers (RRFs) or strongly succinate dehydrogenase-stained vessels (SSVs) demonstrated by muscle biopsy, or the causative mtDNA mutation confirmed by molecular genetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging studies and measurement of blood lactate are useful screening tests for the diagnosis of MELAS, though the definite diagnosis of MELAS relies on the ragged red fibers (RRFs) or strongly succinate dehydrogenase-stained vessels (SSVs) demonstrated by muscle biopsy, or the causative mtDNA mutation confirmed by molecular genetic studies. 10 In 1990, Goto et al 5 first identified the mtDNA A3243G mutation as the molecular basis of MELAS, which was shown to account for more than 80% of the MELAS patients. 11 However, at least 20 other distinct pathogenic mtDNA mutations have been reported in the other 20% patients with MELAS in the past two decades, 12 suggesting great heterogeneity in the genotype of MELAS.…”
Section: Introductionmentioning
confidence: 99%